Professional risk assessment during performing official duties of station dis-patchers on prydniprovsk railway - Nykyforova, O. A.; Sydorenko, H. H. (Science and Transport Progress, 2014)
Purpose. To substantiate the importance of psychophysiological selection for the traffic safety prevention, increase of the human factor reliability on the basis of erroneous actions analysis of the Prydniprovsk railway workers of operator type and literature data. Methodology. Studies have been conducted among operation personnel (station dispatchers) (n = 62), 32 − women, 30 − men. The method of social survey, psychological techniques using the personal, «NPN-A» (neuropsychic instability − accentuations), individual and typological questionnaire were used. Findings. Typical mistakes of Prydniprovsk railway workers of operator type were analyzed. It was found out that a large group of errors is connected with the failure of staff job descriptions and requirements of labor protection instructions, negligence and carelessness, irresponsible attitude to their duties, inadequate personnel training. Originality. The necessity of new approaches development to the systematic analysis on a quantitative basis of management and assessment of the human factor reliability, which can be provided by professional psychophysiological selection of persons related to traffic safety was grounded. Practical value. The obtained results can be the basis for the development of new methods of physiological investigations concerning occupational selection of railway workers of leading professions. It would accurately predict the performance and reliability of the operators and would provide an opportunity to identify contraindications to the professional activity.